Dimensional Speech Emotion Recognition: a Bimodal Approach - Guder, Larissa; Aires, João Paulo; Griebler, Dalvan (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.244402, 2024)
Considering the human-machine relationship, affective computing aims to allow computers to recognize or express emotions. Speech Emotion Recognition is a task from affective computing that aims to recognize emotions in an audio utterance. The most common way to predict emotions from the speech is using pre-determined classes in the offline mode. In that way, emotion recognition is restricted to the number of classes. To avoid this restriction, dimensional emotion recognition uses dimensions such as valence, arousal, and dominance, which can represent emotions with higher granularity. Existing approaches propose using textual information to improve results for the valence dimension. Although recent efforts have tried to improve results on speech emotion recognition to predict emotion dimensions, they do not consider real-world scenarios, where processing the input in a short time is necessary. Considering these aspects, this work provides the first step towards creating a bimodal approach for Dimensional Speech Emotion Recognition in streaming. Our approach combines sentence and audio representations as input to a recurrent neural network that performs speech-emotion recognition. We evaluate different methods for creating audio and text representations, as well as automatic speech recognition techniques. Our best results achieve 0.5915 of CCC for arousal, 0.4165 for valence, and 0.5899 for dominance in the IEMOCAP dataset.